New simple bounds for standard normal distribution function - Ananbeh, Enas A.; Eidous, Omar M. (Communications in statistics. Simulation and computation, 2025)
This paper presents new simple lower and upper bounds for the cumulative normal distribution function, Φ ( z ) . The accuracy and closeness of the proposed bounds to the exact Φ ( z ) are investigated based on the maximum absolute error and the mean absolute error. It is found that the maximum absolute error of the proposed lower bound is 8.55 × 10 − 3 and it is 4.1 × 10 − 4 for the upper bound. In addition, based on 5001 values between z = 0 and z = 5 with step 0.001, we found that the mean absolute error is 3.27 × 10 − 3 for the lower bound and it is 1.1 × 10 − 4 for the upper bound and these two values decrease with increasing the z value.